Prognostic significance of inflammation-related and electrolyte laboratory variables in patients with malignant pleural mesothelioma - Zhang, Yuan; Li, Jie; Zhang, Shu (Frontiers in Medicine, 2023)
Objective Malignant pleural mesothelioma (MPM) is a kind of pleural cancer characterized by low incidence but high invasiveness. There is heterogeneity in survival among patients with MPM. Inflammation-related and electrolyte laboratory variables were previously reported as potential predictors of survival. We evaluated the relationship between overall survival and pre-treatment biomarkers. Materials and methods Patients diagnosed with MPM in Beijing Chaoyang Hospital for more than 10 years were screened for this study. All basic, clinical, radiologic and laboratory variables were collected. The COX univariable and multivariable analysis were used to explore prognostic related risk factors. Results Ninety patients with MPM were included. The median follow-up of all patients was 57 months [interquartile range (IQR): 27–100 months]. The median survival time was 24 months (IQR: 12–52 months). Univariate survival analyses indicated that age, Eastern Cooperative Oncology Group Performance Status, treatment, erythrocyte sedimentation rate, calcium, lymphocyte, hemoglobin, platelet-to-lymphocyte ratio (PLR), and monocyte-to-white blood cell ratio (MWR) were significantly related to survival. Multivariable analysis demonstrated that age [hazard ratio (HR), 2.548; 95% confidence interval (CI) 1.145–5.666; p = 0.022], calcium (HR, 0.480; 95% CI 0.270–0.855; p = 0.013), PLR (HR, 2.152; 95% CI 1.163–3.981; p = 0.015), and MWR (HR, 3.360; 95% CI 1.830–6.170; p < 0.001) might have a significant impact on the prognosis. Conclusion Calcium, MWR, and PLR might be related to the prognosis of MPM patients. Analyzing the relationship between the results of inflammation-related and electrolyte laboratory variables in peripheral blood and prognosis could help clinicians evaluate the situation of patients.